Can Doll therapy preserve or promote attachment in people with cognitive, behavioral, and emotional problems? A pilot study in institutionalized patients with dementia - Pezzati, Rita; Molteni, Valentina; Bani, Marco; Settanta, Carmen; Di Maggio, Maria Grazia; Villa, Ivan; Poletti, Barbara; Ardito, Rita B. (Frontiers in Psychology, 2014)
Doll therapy is a non-pharmacological intervention aimed at reducing behavioral and psychological disorders in institutionalized patients with dementia. This therapy as a care tool has been integrated into the context of long-term care institutions, in which the need to find solutions to cognitive, behavioral and emotional problems showed by people with dementia meets the primary objective of developing good care practices focusing on patients and their needs. In the present work we adopt the Bowlby’s theory of attachment to investigate the effectiveness of Doll therapy. The hypothesis that we here propose is that the emotional experience of the person with dementia during Doll therapy activates caregiving and exploration systems together with the attachment one. To test this hypothesis we compared institutionalized patients with dementia undergoing Doll therapy with a control group and assessed measures of the relational dimension with the environment, such as gaze direction, behaviors of exploration, and behaviors of caregiving. We used an experimental protocol consisting of 10 non-consecutive sessions structured with the goal of recreating a situation of (1) separation from a known figure and (2) interaction with the environment in order to partially recreate the prototypical phases of the ‘Strange situation’. All sessions were videotaped and analyzed through an observational grid. Results support the effectiveness of Doll therapy in promoting and maintaining the affective-relational dimension of attachment-caregiving and the attentive dimension of exploration in patients with advanced stage of dementia. Thus, our results suggest that the use of Doll therapy promotes clinically significant improvements in the ability to relate with the surrounding world. This may be important for managing and caring for patients with dementia in institutionalized context.